2009
DOI: 10.1017/s1368980008002656
|View full text |Cite
|
Sign up to set email alerts
|

Underweight, overweight and obesity among South African adolescents: results of the 2002 National Youth Risk Behaviour Survey

Abstract: Objective: The present paper reports the prevalence of underweight, overweight and obesity by gender, ethnicity and grade, among participants in a 2002 national survey among South African school-going youth that included height and weight measurements. Design: A stratified two-stage sample was used. Nationally representative rates of underweight, overweight and obesity were calculated using weighted survey data and compared using x 2 analysis. Setting: In all, 9224 grade 8 to grade 11 students, present at scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
121
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(143 citation statements)
references
References 10 publications
17
121
2
1
Order By: Relevance
“…Students belonging to higher SES (private schools, higher assets) had significantly higher prevalence of OW/OB compared with those from public schools and with lower assets (2) . This pattern is similar to that observed in adolescents in Mexico (14,15) , India (16) and South Africa (18,19) .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Students belonging to higher SES (private schools, higher assets) had significantly higher prevalence of OW/OB compared with those from public schools and with lower assets (2) . This pattern is similar to that observed in adolescents in Mexico (14,15) , India (16) and South Africa (18,19) .…”
Section: Discussionsupporting
confidence: 87%
“…On the basis of data from economically developing countries (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) , we hypothesized that children from a…”
Section: Snacks Traditional Diet Food Patterns Nutrition Transitionmentioning
confidence: 99%
“…A recent systematic review (38) found that use of BMI-for-age with the Cole 2007 and IOTF 2000 method was a highly conservative approach to defining obesity, with generally much lower estimates of obesity prevalence when used in school-aged children than when national reference data and definitions based on BMI were used. Monasta et al (21,(39)(40)(41)(42)(43) . Recent South African prevalence studies have used anthropometric methods exclusively, the BMI-for-age NCHS/WHO growth reference 1977 data for underweight and the IOTF approach for overweight/obesity (8,30,43) .…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
“…Monasta et al (21,(39)(40)(41)(42)(43) . Recent South African prevalence studies have used anthropometric methods exclusively, the BMI-for-age NCHS/WHO growth reference 1977 data for underweight and the IOTF approach for overweight/obesity (8,30,43) . These studies all used simple proxy measures for body composition and none has used the new Cole et al thinness definition (29) .…”
Section: Main Findings and Implicationsmentioning
confidence: 99%
“…In a life-stage characterised by significant growth and development and the associated changes in body composition, it is not surprising that adolescence is a focus of research relating to overweight and obesity. Reddy et al (1) report on data from a South African survey of 9224 adolescent schoolaged children and describe differences in the distribution of overweight and obesity by sex, racial heritage and socio-economic status. In a country in nutrition transition experiencing both forms of malnutrition, they conclude that ongoing surveillance of malnutrition mindful of gender, racial and socio-economic disparities is important.…”
Section: In This Issuementioning
confidence: 99%